Effect of Tooth Wear on the Technological Parameters of the Milling Process of Asphalt Concrete Layers - Marius Gabriel Petrescu; Teodor Dumitru; Eugen Laudacescu; Maria Tănase (Lubricants)
This article discusses the findings of an experimental study designed to investigate the cutting forces encountered during the milling of asphalt pavement, considering the influence of cutter teeth wear. Experimental research was carried out for different values of wear, considered as a change in the shape of the active part of the tooth and a reduction in its height. The aspects studied continue the previous research of the authors regarding the study of cutting forces when milling asphalt pavement, using new milling teeth (without wear). Through this new study, the authors want to highlight how the phenomenon of wear influences the mechanical conditions of the chipping process and the efficiency of asphalt pavement processing. The experimental research was performed using an original stand, designed by the authors of the article, equipped with instruments for recording the values of the cutting force in the direction of advance. The experimental part is completed by the numerical modeling using the discrete element method (DEM). Research has shown that the increase in cutting forces is more pronounced at low advanced speed. Increasing the advanced speed leads to a reduction in differences between the cutting forces corresponding to the use or not of the milling tooth wear compensation. The study’s findings offer valuable insights into how milling parameters influence cutting forces, providing a basis for optimizing asphalt pavement milling processes.